Metoprolol protects against myocardial infarction by inhibiting miR‐1 expression in rats. (8th November 2019) - Qin, Wei; Zhang, Longyin; Li, Zhange; Xiao, Dan; Zhang, Yue; Yang, Huan; Zhang, Haiying; Xu, Chaoqian; Zhang, Yong
Abstract: Objectives: Metoprolol is regarded as a first‐line medicine for the treatment of myocardial infarction (MI). However, the underlying mechanisms remain largely unknown. This study aimed to investigate the involvement of miR‐1 in the pharmacological function of metoprolol. Methods: In vivo MI model was established by left anterior descending coronary artery (LAD) ligation. The effects of metoprolol on infarct size and cardiac dysfunction were determined by triphenyltetrazolium chloride staining and cardiac echocardiography, respectively. In vitro oxidative stress cardiomyocyte model was established by H2 O2 treatment. The effect of metoprolol on the expression of miR‐1 and connexin43 (Cx43) was quantified by real‐time PCR and western blot, respectively. The intercellular communication was evaluated by lucifer yellow dye diffusion. Key findings: Left anterior descending ligation‐induced MI injury was markedly attenuated by metoprolol as shown by reduced infarct size and better cardiac function. Metoprolol reversed the up‐regulation of miR‐1 and down‐regulation of Cx43 in MI heart. Moreover, in H2 O2 ‐stimulated cardiomyocytes, overexpression of miR‐1 abolished the effects of metoprolol on Cx43 up‐regulation and increased intercellular communication, indicating that miR‐1 may be a necessary mediator for the cardiac protective function of metoprolol. Conclusions: Metoprolol relieves MI injury via suppression miR‐1, thus increasing its target protein Cx43 and improving intercellular communication.